The Effect of Pruning and Several Kinds of Growing Media Fertigation Hydroponic Systems Against Protection and Production of Melons (Cucumis Melo L.) - M Abror; M Koko Ardiansyah (Nabatia, 2016)
This study aims to determine the effect of trimming with a wide variety of growing media hydroponic system fertigation on growth and yield of melon. Research will be conducted in the green house (House of plastic) UMSIDA Agriculture Faculty, Campus 2, Gelam, Candi, Sidoarjo, research time between the months of March to June 2016 using analysis of variance and continued test HSD 5%. The variables measured were plant height, leaf number, level of sweetness of fruit, fruit weight, high-fruit, thickness of the flesh of the fruit, conclusion from this research is going on the effect of trimming and a wide variety of growing media hydroponic system fertigation in treatment PM5 (trimming down, kokopit). There was also a real influence on the treatment PM6 (without pruning, kokopit) .In observation of plant height, leaf number, fruit weight, and high fruit. And also happens to influence a wide range of growing media on growth and yield of melon on hydroponics fertigation system, the PM6 treatment (without pruning, kokopit) had the highest rates in the observation of plant height, weight of the fruit, and the number of leaves.